2011
DOI: 10.1126/science.1208710
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Molecular Preorganization for Chirality Transfer on a Catalyst Surface

Abstract: The chemisorption of specific optically active compounds on metal surfaces can create catalytically active chirality transfer sites. However, the mechanism through which these sites bias the stereoselectivity of reactions (typically hydrogenations) is generally assumed to be so complex that continued progress in the area is uncertain. We show that the investigation of heterogeneous asymmetric induction with single-site resolution sufficient to distinguish stereochemical conformations at the submolecular level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 37 publications
8
136
3
Order By: Relevance
“…Further work has shown that other polar species, such as water, can also cause bitartrate to restructure its adsorption footprint, implying that the chiral surface will be highly dynamic when other polar co-adsorbates are present. Such a dynamic local response has significant implications in systems where the bitartrate species acts as a chiral modifier during heterogeneous enantioselective catalysis, 3,4 for example in hydrogenation over tartaric acid modified RANEY s nickel catalysts. Although these systems show no long range order, experiments find enantioselective reaction is accelerated by a direct hydrogen-bonding interaction between the bitartrate modifier and the substrate molecule, 48 implying a local ordering of the reaction complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work has shown that other polar species, such as water, can also cause bitartrate to restructure its adsorption footprint, implying that the chiral surface will be highly dynamic when other polar co-adsorbates are present. Such a dynamic local response has significant implications in systems where the bitartrate species acts as a chiral modifier during heterogeneous enantioselective catalysis, 3,4 for example in hydrogenation over tartaric acid modified RANEY s nickel catalysts. Although these systems show no long range order, experiments find enantioselective reaction is accelerated by a direct hydrogen-bonding interaction between the bitartrate modifier and the substrate molecule, 48 implying a local ordering of the reaction complex.…”
Section: Discussionmentioning
confidence: 99%
“…The nanoscale control of chiral molecular assembly at surfaces is of central importance in fields as diverse as chiral separations, 1,2 heterogeneous enantioselective catalysis, 3,4 plasmonics, 5 chiroptical switching 6,7 and biosensors. 8 In all cases, the surface function is profoundly influenced by how individual enantiomers organize at the local and the global level, therefore the outstanding problem in the field is to understand the factors that drive enantiomer assembly and segregation.…”
Section: Introductionmentioning
confidence: 99%
“…It is typically assumed that NEA, like the cinchona alkaloids, forms a one-to-one complex with the reactant to force it into a specific adsorption geometry on the surface of the metal. [11] However, there is also evidence to suggest that NEA may form supramolecular surface ensembles with chiral pockets available for the adsorption of prochiral reactants. [10,28] That mechanism is consistent with the amine-dominated adsorption mode established in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The activation energies calculated confirm that that self-assembly of glycine on low-index copper surfaces is indeed an activated process, which is facile in the temperature range (typically from 300 K to 420 K) generally employed in experiments. We suggest that the walking mechanism predicted in this study might play a key role in the formation of similar self-assembled systems relevant for nanotechnology and surface chemistry, such as thiolates 38 , amines 39 or chiral organic acids 40 on metal surfaces.…”
Section: Discussionmentioning
confidence: 99%